FINANCIAL PERFORMANCE ANALYSIS OF PUBLIC HOSPITALS BEFORE AND DURING THE COVID-19 PANDEMIC - Rexana, Fritzie A.; Widjaja, Indra (Graduate Program of Universitas Tarumanagara, 2023)
This study is purposed to analyze the financial performance of public hospitals companies registered at the Indonesian Stock Exchange before and during the Covid-19 Pandemic. This study shows the difference of financial performance and financial ratio's changes within hospital due to the Covid-19 condition. The method of this study is quantitative. The data used are secondary data from financial reports of hospital between the period of second quarter of 2019 until first quarter of 2021. Financial performance of hospital is measured from statistical calculation on Current Ratio, Quick Ratio, Debt-to-Equity Ratio, Debt Ratio, Total Asset Turnover, Inventory Turnover, Net Profit Margin, and Return on Equity before and during the Covid-19 Pandemic. Result of Normality Data Test by using Kolmogorov Smirnov shows that asymp sig is < 0.05, so H0 is accepted and H1 is rejected, thus not normally distributed. Continued with the Wilcoxon Test with average rank of not so much different. Also, Statistical Test shows that asymp sig for each financial ratio is > 0.05, so that the hypothesis is rejected and thus can be concluded that the financial performance of public hospitals companies registered at Indonesian Stock Exchange are not significantly different. The changes of financial ratios of public hospitals due to Covid-19 Pandemic condition are noticeable in the decreasing of profitability ratio. This shows that public hospitals are in the conditions of the Covid-19 Pandemic, although hospital capacity looks overloaded, in terms of profitability, it has decreased, this can be due to the increasing operational burden of hospitals with special policies during the pandemic. Meanwhile, in terms of other financial ratios, the condition of the Covid- 19 Pandemic did not make the hospital's financial performance better than before the Covid-19 Pandemic.